MENAKAR STABILITAS HEGEMONI BAGI PENYELESAIAN KONFLIK ROHINGYA - Tety Rachmawati (UNIDA Gontor, 2017)
This paper tried to explain the importance of Hegemonic stability to resolve conflict in Rohingya and also to see ASEAN countries opportunities to be hegemony power, so that they are influential to implementation ASEAN rule particularly in Rohingya conflict resolution. The method that is used in this research is qualitative in descriptive-analytic explanation. Theoretically, hegemony power was needed to create international system stability as well as to create the security in the region. Rohingya conflicts caused many people to evacuate themselves to neighbor countries. This condition caused security in the region became not stable. Therefore, it needed hegemony power to create stability in the region. The country which has strongest power was able to influence other countries. If it was compared to other ASEAN countries, Singapore is the most powerful country in ASEAN. Singapore is one of country that has the biggest military power, advance economic and stable political situation. However, Singapore has weakness as the smallest country with small populations, so that it is not too influential in ASEAN institution. Singapore did not have enough opportunity to become hegemony power to control instability that was caused of Rohingya conflict.